Children’s accounts of labelling and stigmatization in private schools in Delhi, India and the Right to Education Act - Lafleur, Michael; Srivastava, Prachi (Education Policy Analysis Archives, 2019)
India’s Right of Children to Free and Compulsory Education Act, 2009 compels private schools to reserve a proportion of their seats for free for disadvantaged children. Although controversial, it is idealized as an equity measure for inclusion in and through education. This small-scale study, feeding into a larger research project, details children’s accounts of their everyday lived experiences at private schools in Delhi. Children reported labelling students by teachers as ‘naughty’ or academically ‘weak’ or ‘incapable’ as a pervasive practice. These ‘designated identities’ (Sfard & Prusak, 2005) were reinforced by teachers and through peer interactions. They were internalized by participants about their peers and affected how they interacted with them. Peers who were labelled were reported to be stigmatized. Surprisingly, neither caste nor gender were mentioned as explicitly marking participant experiences. The paper also discusses the participatory methods employed in the study as a further contribution to the literature on private schooling. Data are from participatory ‘draw-and-talk’ sessions conducted with 16 children in 2015-16 from marginalized backgrounds, accessing six different private schools in one catchment area, half of whom secured a free private school seat. Participants were from amongst the first cohorts eligible for the free seats provision.